Knowledge, Attitude and Practices on the Use of Asthma Action Plans among Adult Asthmatic Patients Aged 18-65 in Nyamira, Kenya. - (:unkn) unknown (International Journal of TROPICAL DISEASE & Health, 2023)
Introduction: Globally the World Health Organization (WHO) estimates that up to 334 million people suffer from asthma. In Kenya it is estimated that about 10% of the Kenyan population, or 4 million people, have asthma. Aim: The objective of this study was to assess knowledge, attitude and practices of patients 18-65 on the use of personized asthma action plans in Nyamira County. Methodology: Cross-sectional study design was employed in this research. Participants were selected using systematic sampling. Significant differences in categorical variables were found using the Chi-square and Fisher's Exact Test. The threshold for statistical significance was set at p<0.05. Results: The study sample size was 220 asthma patients. The majority of responders 72.7% were unaware of PAAPs. Concerning attitude, most of participants had a negative attitude about the use of PAAPs, believing that they should only be used by the extremely ill 63.6%. Poor practices were seen among the patients who had access to these tools, with 39.0% checking them at home and 61.0% never checking them at all. Statistically there were significant association between the various patients’ factors influencing use of asthma action plans among adult asthmatic patients with a p = 0. 021. Conclusion: The majority of the patients 76.4% who participated in this research did not use the personalized asthma action plan cards. Additionally, the majority of participants reported poor practices on PAAPs, low levels of awareness, and negative attitudes. To combat the low-level knowledge, negative attitude, and poor practices among asthma patients, the ministry of health should raise awareness about the use of PAAPs.
Keywords: PAAPs-personalized asthma action plans; respiratory condition breath; chest tightness.